GM-020 Seamless care: Development of a discharge communication tool for elderly patients. (14th February 2016) - Giraud, J; Thevenet, M; Haddad, R; Leveque, S; Mion, M; Rieutord, A
Abstract : Background: Hospital discharge is a critical transition point for many inpatients, particularly elderly patient who are especially vulnerable. One of the main related cause is lack of coordination between the hospital and community healthcare professionals and caregivers. In our local territory (500 000 inhabitants, 14 cities), we have decided to improve coordination by focusing on communication. Purpose: The aim was to design, evaluate and compare a new discharge communication tool (NCT), according to the needs of the community caregiver and hospital professionals, with the classic institutional discharge form. Material and methods: Group meetings, interviews and brainstorming sessions were organised to elaborate this NCT. Qualitative and quantitative methods were used to compare the two tools over 4 weeks, in the acute geriatric unit (AGU). Short answers and tick boxes were chosen to quickly screen patient information at discharge through 6 professional domains. Finally, we evaluated global satisfaction of NCT among community and hospital professionals by anonymous questionnaire or phone interviews. Results: 78 elderly patients were discharged from AGU. The main significant difference between the two communication tools was the transmission rate of these documents at discharge (70% for NCT vs 0%). The final reception rate by the final home based caregiver was 64% for the NCT. The NCT was significantly more completed, although it was sometimes partially completed. Nurses and nurses' aides were the most implicated; physiotherapists had the best total level. However, geriatricians were not committed to this new process. Concerning professional satisfaction: community professionals were satisfied to very satisfied by the information transmitted which was considered clear and easy to read. On the hospital side, they considered the NCT easier and quicker to fill, clearer than the old version, and declared that it was significantly less time consuming than previously (5% vs 70%). Conclusion: This first collaborative and pilot study allowed us to pool energies from community and hospital professionals to develop a practical and useful communication tool to improve elderly patient discharge. This contributes to the elimination of existing silos all along the care process of the elderly patient and acknowledges the equal importance of each caregiver. More developments are warranted to further improve the availability rate of NCT to the final caregiver. No conflict of interest.